2003
DOI: 10.1897/1551-5028(2003)022<1350:eotagp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF THE ANDROGENIC GROWTH PROMOTER 17-Β-Trenbolone ON FECUNDITY AND REPRODUCTIVE ENDOCRINOLOGY OF THE FATHEAD MINNOW

Abstract: Trenbolone acetate is a synthetic steroid that is extensively used in the United States as a growth promoter in beef cattle. The acetate is administered to livestock via slow-release implants; some is converted by the animal to 17-beta-trenbolone, a relatively potent androgen receptor agonist in mammalian systems. Recent studies indicate that excreted 17-beta-trenbolone is comparatively stable in animal waste, suggesting the potential for exposure to aquatic animals via direct discharge, runoff, or both. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
192
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(210 citation statements)
references
References 39 publications
16
192
2
Order By: Relevance
“…The basis of the approach lies in evaluating whether test chemicals block occurrence of an in vivo response mediated through the AR. Studies in our lab and elsewhere have shown that the synthetic androgen 17␤-trenbolone (TB) binds with high affinity to fish AR(s) and masculinizes female fish at concentrations in water in the range of 20-50 ng/L (Ankley et al, 2003;Wilson et al, 2004;Seki et al, 2006). In the fathead minnow, masculinization is manifested by a proliferation and thickening of the dorsal pad and the de novo development of craniofacial nuptial tubercles, external structures which can be visually detected and easily quantified ).…”
Section: Introductionmentioning
confidence: 99%
“…The basis of the approach lies in evaluating whether test chemicals block occurrence of an in vivo response mediated through the AR. Studies in our lab and elsewhere have shown that the synthetic androgen 17␤-trenbolone (TB) binds with high affinity to fish AR(s) and masculinizes female fish at concentrations in water in the range of 20-50 ng/L (Ankley et al, 2003;Wilson et al, 2004;Seki et al, 2006). In the fathead minnow, masculinization is manifested by a proliferation and thickening of the dorsal pad and the de novo development of craniofacial nuptial tubercles, external structures which can be visually detected and easily quantified ).…”
Section: Introductionmentioning
confidence: 99%
“…Field observations have documented 1,700 ng l À 1 17a-TBOH in manure lagoons 9 , and 55 ± 22 ng g À 1 in solid manure and surface soils 10 . TBA metabolite exposure is problematic for ecosystem health because 17a-TBOH and 17b-TBOH are potent endocrine disruptors, with exposure to as little as 10-30 ng l À 1 significantly reducing fecundity, resulting in phenotypic sex reversal in fish, or altering endocrine function [11][12][13] .…”
mentioning
confidence: 99%
“…Further work extended this basic design to EDC-oriented tests with other small fish species, including the medaka (Oryzias latipes) and zebrafish (Danio rerio) [4]. As part of the validation of the 21-d assay, several model chemicals were tested, including estrogen receptor agonists such as 17b-estradiol and methoxychlor [2,3] and androgen receptor agonists such as methyltestosterone and 17b-trenbolone [3,5]. Tyler et al [6] described a test method specific for estrogens that focused on the induction of vitellogenin in fathead minnow early life stages, an approach that aligned well with the commonly utilized 30-d survival and growth assay in this species and also was recommended as a reasonable design for detecting estrogenic EDCs [1].…”
mentioning
confidence: 99%